Behavioral and neurochemical characterization of new mouse model of hyperphenylalaninemia. - Tiziana Pascucci (Public Library of Science (PLoS), 2013)
Hyperphenylalaninemia (HPA) refers to all clinical conditions characterized by increased amounts of phenylalanine (PHE) in blood and other tissues. According to their blood PHE concentrations under a free diet, hyperphenylalaninemic patients are commonly classified into phenotypic subtypes: classical phenylketonuria (PKU) (PHE > 1200 µM/L), mild PKU (PHE 600-1200 µM/L) and persistent HPA (PHE 120-600 µM/L) (normal blood PHE < 120 µM/L). The current treatment for hyperphenylalaninemic patients is aimed to keep blood PHE levels within the safe range of 120-360 µM/L through a PHE-restricted diet, difficult to achieve. If untreated, classical PKU presents variable neurological and mental impairment. However, even mildly elevated blood PHE levels, due to a bad compliance to dietary treatment, produce cognitive deficits involving the prefrontal cortical areas, extremely sensible to PHE-induced disturbances. The development of animal models of different degrees of HPA is a useful tool for identifying the metabolic mechanisms underlying cognitive deficits induced by PHE. In this paper we analyzed the behavioral and biochemical phenotypes of different forms of HPA (control, mild-HPA, mild-PKU and classic-PKU), developed on the base of plasma PHE concentrations. Our results demonstrated that mice with different forms of HPA present different phenotypes, characterized by increasing severity of behavioral symptoms and brain aminergic deficits moving from mild HPA to classical PKU forms. In addition, our data identify preFrontal cortex and amygdala as the most affected brain areas and confirm the highest susceptibility of brain serotonin metabolism to mildly elevated blood PHE.